DESCENTRALIZACIÓN Y CAMINO HACIA LA GOBERNANZA EN EL CANTÓN DE COTO BRUS - Fernández, Luis Fernando (2012)
This article is written as part of a new process promoted by the 8801 law, about decentralization, which seeks to generate cantonal governance processes, as against a time trend of blunders and political patronage that delegitimize the effectiveness of centralist intentionality in Costa Rica. The new experiences look for local governments to generate leadership in coordination with public institutions present in the canton. The process requires high quality information generated at community level, district councils, development associations, boards of education, health boards and other productive organizations participating in the discussions of local issues, to provide ideas and actions for solutions, to promote open innovation and social and institutional flows are controlled. The question that arises from the process is: How does the political and institutional weight to hold the powers of the interagency coordinating committees for cantons influence the course of the cantons and encourage institutional cooperation in local development?